Identities of Degenerate Poly-Changhee Polynomials Arising from λ-Sheffer Sequences - Sang Jo Yun; Jin-Woo Park (Journal of Mathematics)
In the 1970s, Gian-Carlo Rota constructed the umbral calculus for investigating the properties of special functions, and by Kim-Kim, umbral calculus is generalized called λ-umbral calculus. In this paper, we find some important relationships between degenerate Changhee polynomials and some important special polynomials by expressing the Changhee polynomial as a linear combination of some special polynomials. In addition, we derive some interesting identities related to degenerate poly-Changhee polynomials and some important special functions by using λ-umbral calculus.